Coping Strategies and Psychopathological Responses Among Medical and Non-medical Professionals – a Cross-Sectional Online Survey - Ciułkowicz, Marta; Maciaszek, Julian; Misiak, Błażej; Pałȩga, Anna; Rymaszewska, Joanna; Szcześniak, Dorota Maria (Frontiers in Psychiatry, 2021)
Background: The SARS-CoV-2 pandemic was announced on March 11th, 2020, due to a surge of newly confirmed cases that significantly impacted populations worldwide, both directly and indirectly. Based on past epidemics research, the mental health implications of introduced restrictions should be expected and adequately addressed irrespective of the practiced profession. Objective:  The study aimed to explore psychopathological responses, including post-traumatic stress disorder (PTSD), concerning coping strategy clusters during the COVID-19 pandemic among medical and non-medical workers. Methods: A cross-sectional web survey of the general population was performed from 16th March to 26th April 2020 in Poland during the first peak of COVID-19 cases. A sample of 1831 professionally active respondents, 64.0% of which pursuing a medical career, filled out General Health Questionnaire-28 (GHQ-28), The Impact of Event Scale-Revised (IES-R), and MiniCOPE along with the author’s questionnaire exploring sociodemographic data and work-related possibility of direct exposure to contagion and availability of proper protection, contact with the infected without accurate protective measures as well as the adequacy of workers when compared settings. Results: Individuals labeled with specific clusters had significantly different psychopathological manifestations. Maladaptive cluster associated with significantly higher GHQ-28 and IES-R scores on both total subscales and all subscales compared to those representing the non-specific and adaptive cluster. Similar findings were observed concerning the frequency of the GHQ-28 positive score. The non-specific cluster was associated with significantly higher GHQ-28 total scores and scores for social dysfunction and severe depression than the adaptation cluster. In turn, the IES-R score of avoidance was significantly higher in respondents representing the adaptive cluster than in those from the non-specific cluster. Medical professionals from the adaptive cluster scored significantly higher on the GHQ-28 social dysfunction and severe depression subscales compared to those from the non-specific cluster. Similar results were obtained in non-medical professionals. Conclusions: Positive screening for psychopathological and PTSD symptoms was expected regardless of the coping strategies used in both analyzed groups. Given the dramatically developing situation of the COVID-19 pandemic, support initiatives grounded in research evidence may be essential for maintaining the mental well-being and resilience of both the medical and non-medical workforce.